2016
DOI: 10.9790/0853-50768690
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Hematological Changes in Childhood Malaria in India

Abstract: Malaria caused by Plasmodium species is a disease with high morbidity and mortality, especially in children. The changing clinical and blood manifestations of P.falciparum, emerging trends of complications with P.vivax are some of the important issues that merit attention at present in India. The prospective crosssectional study conducted on 170 patients of malaria in Mumbai aimed at studying the clinico-haematological alterations in the disease. Fever and splenomegaly were critical findings in majority of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Study done in Ethiopia observed that the thrombocytopenia was found in 56.8%, while mild, moderate, and severe thrombocytopenia accounted for 41.6%, 45.3% and 13.1% (23). Similar studies in endemic area found the severe thrombocytopenia was 8.8% in 45.6% of thrombocytopenia in France, 14.1% in 43.6% of thrombocytopenia in Senegal, 14.8% and in 58% of thrombocytopenia in Libreville (Moulin et al, 2003), 5% in 49% of thrombocytopenia in Kenya (30), 1.5% in 48.6% of thrombocytopenia in Colombia (31), and 12.9% in 68.7% of thrombocytopenia in India (32). Similar previous studies observed that the thrombocytopenia was significantly more frequent and more profound in those with SM than in those with mild forms (31,33).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Study done in Ethiopia observed that the thrombocytopenia was found in 56.8%, while mild, moderate, and severe thrombocytopenia accounted for 41.6%, 45.3% and 13.1% (23). Similar studies in endemic area found the severe thrombocytopenia was 8.8% in 45.6% of thrombocytopenia in France, 14.1% in 43.6% of thrombocytopenia in Senegal, 14.8% and in 58% of thrombocytopenia in Libreville (Moulin et al, 2003), 5% in 49% of thrombocytopenia in Kenya (30), 1.5% in 48.6% of thrombocytopenia in Colombia (31), and 12.9% in 68.7% of thrombocytopenia in India (32). Similar previous studies observed that the thrombocytopenia was significantly more frequent and more profound in those with SM than in those with mild forms (31,33).…”
Section: Discussionsupporting
confidence: 56%
“…Thrombocytopenia had strong negative correlation with parasitemia (r -0.335, P value 0.000), and parasite count (r -0.268, P value 0.000). Previous studies concluded that the thrombocytopenia is associated with peripheral parasitemia levels (14,30,32,(34)(35)(36). The average of platelets count among Group 2 was lower than Group 2 (P value 0.000).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the hematological examination of patients with malaria can be influenced by several factors, including the level of regional endemicity, the background of hemoglobinopathies, demographic factors and immunity to malaria, but this is not yet known with certainty due to the complex pathogenesis process [13].…”
Section: Introductionmentioning
confidence: 99%